Growing Significance of EU Institutions in Promotion of Inter-regional policies - E. V. Ermakova (Vestnik MGIMO-Universiteta, 2014)
The article explores the variety of tools and vehicles applied within the EU to expand the prerogative of the regions of the EU member states. The author uses as an example the inter-regional policies in Belgium in respect of the Flemish Region and the Walloon Region. The author analyzes the mechanisms of promotion of external regional relations in Belgium as a means of addressing different problems both on national and all-European level, supporting the arguments and conclusions by examples of relevant EU initiatives. The article details the activities of the EU Regional Committee (RC), the EU advisory body with the powers of political initiative, upholding the principle ofsubsidarity in the implementation of the EU member states' regional policies. The involvement of the Flemish Region and the Walloon Region in the activities of EU RC is described and summarized. As a case study, the article deals with Belgium's rotating six months presidency in the EUin 2010 when the country, which was going through a severe political crisis with no federal government in place, was represented by the two regions. The special focus of the article is on the strategic EU program "Europe2020" and its implementation by the regions of Belgium. There is an account of the initiatives undertaken by the Flemish Region and the Walloon Region within the framework of this program outlining the interaction of the two regions. The author provides a comprehensive analysis of the involvement of the Flemish Region and the Walloon Region with various EU institutions describing how each party achieves the promotion of its regional interests. Within this context, it is a noteworthy development that the Flemish Region is participating in the international program "Pact 2020" on energy all by its own. The article features quotations by Flemish and Walloon political figures which serve as an illustration of the prevailing attitudes in the Belgian society to the process of regionalization of their country. The EU structural funds aimed at funding these policies play a crucial role in the maturing of the regional dimension of the activities pursued by the EU institutions. The author finalizes with the review of the EU reasons for placing high importance on the promotion of the development of inter-regional ties between member states.